Risk Factors for Obstetric Fistula in Western Uganda: A Case Control Study - Barageine, Justus Kafunjo (PLoS One, 2014)
INTRODUCTION: Two million women worldwide are living with genital fistula with an annual incidence of 50,000–100,000 women. Risk factors for obstetric fistula are context bound. Studies from other countries show variation in the risk factors for obstetric fistula. This study was conducted to identify risk factors for obstetric fistula in western Ugandan context. METHODS: A case control study comparing background factors of women with obstetric fistula (cases) and women without fistula (controls) was conducted in western Uganda. Data was collected using face-to-face interviews. Univariate, bivariate and multivariate analysis was conducted using Stata 12. RESULTS: Altogether, 420 respondents (140 cases and 280 controls) participated in the study. Duration of labour was used to form the product terms when assessing for interaction and confounding since it was one the most significant factors at bivariate level with a narrow confidence interval and was hence considered the main predictor. After adjusting for interaction and confounding, significant risk factors associated with development of obstetric fistula in western Uganda were: Caesarean section (adjusted odds ratio [AOR]  = 13.30, 95% CI  = 6.74–26.39), respondent height of 150 cm or less (AOR  = 2.63, 95% CI  = 1.35–5.26), baby weight of 3.5 kg or more (AOR  = 1.52, 95% CI  = 1.15–1.99), prolonged labour (AOR  = 1.06, 95% CI  = 1.04–1.08. A quarter of the fistulas had resulted from iatrogenic complication during caesarean section. Compared to no education, post primary level of education was protective against obstetric fistula (AOR  = 0.31, 95% CI  = 0.13–0.72) and there was no difference between respondents without education and those with primary level education. CONCLUSIONS: Surgeons contribute to a big proportion (25%) of fistula cases hence caesarean section being a risk factor in this region. Other risk factors include; prolonged labour, weight of the baby of 3.5 kg or more, respondent height of 150 cm or less (short stature), and low or no education are risk factors for obstetric fistula in western Ugandan.